Initial experience with a novel, modular, minimalistic approach for transfemoral aortic valve implantation. (1st June 2021) - Kim, Won-Keun; Doerr, Oliver; Renker, Matthias; Choi, Yeong-Hoon; Liakopoulos, Oliver; Hamm, Christian W.; Nef, Holger
Abstract: Objectives: We introduce a novel approach that involves a s ingl e arteri al access and low contrast agent volum e (SLIM). Background: Transcatheter aortic valve implantation (TAVI) is subject to an ongoing process of refinement and simplification. Methods: Between January 2019 and November 2020, a total 888 patients with severe aortic stenosis underwent transfemoral TAVI using balloon-expandable or specific self-expanding devices. The study cohort comprised patients with attempted SLIM approach ( n = 291). A matched cohort of patients who were treated in a standard fashion served as control group (n = 291). Results: The SLIM approach was successful in 92.4% of attempted cases. In the SLIM group, utilization of contrast agent (23 [19–37] vs. 75 [52–100] ml; p < 0.001), rates of any acute kidney injury (5.5% vs. 12.7%; p = 0.002), complications at the secondary access (0.3% vs. 3.1%; p = 0.011) and length of hospital stay (7 [5–8] vs. 7 [6–9]) days; p = 0.039) were significantly reduced. All other procedural outcomes were similar between groups. Conclusions: Initial results of this novel, minimalistic approach demonstrate its feasibility and potential beneficial effects without compromising procedural safety. Further refinement of this approach is warranted. Graphical abstract: Unlabelled Image Highlights: SLIM (single-arterial access; low contrast use) was successful in 92.4%. Rates of acute kidney injury and access-site complications decreased. Length of hospital stay was reduced. SLIM did not compromise procedural success and safety.